The Evolution of Dopamine Systems in Chordates - Yamamoto, Kei; Vernier, Philippe (Frontiers in Neuroanatomy, 2011)
Dopamine (DA) neurotransmission in the central nervous system (CNS) is found throughout chordates, and its emergence predates the divergence of chordates. Many of the molecular components of DA systems, such as biosynthetic enzymes, transporters and receptors, are shared with those of other monoamine systems, suggesting the common origin of these systems. In the mammalian CNS, the DA neurotransmitter systems are diversified and serve for visual and olfactory perception, sensory-motor programming, motivation, memory, emotion, and endocrine regulations. Some of the functions are conserved among different vertebrate groups, while others are not, and this is reflected in the anatomical aspects of DA systems in the forebrain and midbrain. Recent findings concerning a second tyrosine hydroxylase gene (TH2) revealed new populations of DA synthesizing cells, as evidenced in the periventricular hypothalamic zones of teleost fish. It is likely that the ancestor of vertebrates possessed TH2 DA-synthesizing cells, and the TH2 gene has been lost secondarily in placental mammals. All the vertebrates possess DA cells in the olfactory bulb, retina and in the diencephalon. Midbrain DA cells are abundant in amniotes while absent in some groups, e.g. teleosts. Studies of protochordate DA cells suggest that the diencephalic DA cells were present before the divergence of the chordate lineage. In contrast, the midbrain cell populations have probably emerged in the vertebrate lineage following the development of the midbrain-hindbrain boundary. The functional flexibility of the DA systems, and the evolvability provided by duplication of the corresponding genes permitted a large diversification of these systems. These features were instrumental in the adaptation of brain functions to the very variable way of life of vertebrates.